Effect of different rest intervals, between sets, on muscle performance during leg press exercise, in trained older women - Jambassi Filho, José C. [UNESP]; Gobbi, Lilian T.B. [UNESP]; Gurjão, André L.D. [UNESP]; Gonçalves, Raquel [UNESP]; Prado, Alexandre K.G. [UNESP]; Gobbi, Sebastião [UNESP] (My University, 2013)
The purpose of this study was to assess the effect of different rest intervals (RI) between sets on number of repetitions, sustainability of repetitions, and total volume during a leg press exercise. Seventeen resistance-trained older women (68.0 ± 5.9 years, 71.2 ± 11.7 kg, 1.58 ± 0.07 m) participated in the study. All participants performed three sets to voluntary exhaustion, with loads that corresponded to 15 maximum repetitions, in two experimental sessions (that ranged from 48 to 72 hours apart). In each session, one of two RI (one-minute: RI-1 and three minute: RI-3) was tested, employing a randomized and counterbalanced design. For both RI, significant reductions (p < 0.05) were observed in the number of repetitions and sustainability of repetitions, from the first to the second and third sets. Differences (p < 0.05) between the RI also were observed in the two final sets. The total volume for the RI-3 session was statistically higher (29.4%, p < 0.05) as compared to the RI-1 session. The length of the RI between sets influenced the number of repetitions, sustainability of repetitions, and total volume. The longer RI should be used, therefore, when the goal of training is to increase the total volume. © Journal of Sports Science and Medicine.
Keywords: Aging; Muscle endurance; Muscle fatigue; Recovery